Limites da indústria cultura cearense do forró à formação humana omnilateral - Albuquerque, Raoni Cunha Aragão de (2020)
This master's research sought to understand how an ancient cultural and festive manifestation of the Brazilian popular classes, called in the mid-nineteenth century forrobodó, and today forró, became, from the twentieth century, a potent commodity at the service of what Adorno and Horkheimer conceived by cultural industry. In Brazil, especially from the 90s onwards, a specific cultural forró industry was developed in Ceará, present in Fortaleza until today, making the research on this object worthy of a more detailed investigation. In addition to the general purpose, we sought to identify whether such a concept by German thinkers applies to the Brazilian reality and to realize if there are contradictions between the great cultural industry and the experiences of dance teachers and musicians who survive from their autonomous work with forró. To achieve these objectives, we sought to exhaust possible determinations of the object through the following categorical premises: artistic-aesthetic, philosophical-sociological and empirical. Thus, we carried out a wide literature review; we sought the etymology of the forró concept and its sociocultural significance through the Brazilian space-time; we cut the perception of forró in the categories of artistic expression and social experience; we carried out semi-structured interviews with dance teachers and musicians who live from their autonomous work with forró. The predominance of this cultural industry was found in popular mega-events, in the mass media and in the general collective imagination of Fortaleza. However, there are also ways to experience forró that escape this aesthetic pattern and conspicuous entertainment. Small concert halls, themed ballroom dancing balls, annual events promoted even by the interviewed workers, show that the contradictions between the hegemonic cultural industry and the popular classes are assimilated in countless ways.